2018
DOI: 10.1371/journal.ppat.1007377
|View full text |Cite
|
Sign up to set email alerts
|

Transcription apparatus of the yeast virus-like elements: Architecture, function, and evolutionary origin

Abstract: Extrachromosomal hereditary elements such as organelles, viruses, and plasmids are important for the cell fitness and survival. Their transcription is dependent on host cellular RNA polymerase (RNAP) or intrinsic RNAP encoded by these elements. The yeast Kluyveromyces lactis contains linear cytoplasmic DNA virus-like elements (VLEs, also known as linear plasmids) that bear genes encoding putative non-canonical two-subunit RNAP. Here, we describe the architecture and identify the evolutionary origin of this tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 86 publications
2
21
0
Order By: Relevance
“…VLE mRNAs also contain 5' poly(A) leaders of variable length that are not complementary to the VLE DNA (27). We provided evidence that 5' poly(A) leaders of VLE mRNAs are formed by a mechanism similar to the synthesis of 5' poly(A) leaders of the VACV postreplicative transcripts (26). We further demonstrated that 5' highly polyadenylated VLE mRNAs do not contain the m 7 G cap moiety at their termini.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…VLE mRNAs also contain 5' poly(A) leaders of variable length that are not complementary to the VLE DNA (27). We provided evidence that 5' poly(A) leaders of VLE mRNAs are formed by a mechanism similar to the synthesis of 5' poly(A) leaders of the VACV postreplicative transcripts (26). We further demonstrated that 5' highly polyadenylated VLE mRNAs do not contain the m 7 G cap moiety at their termini.…”
mentioning
confidence: 73%
“…The exact biological role of the 5' poly(A) leaders in postreplicative transcripts has not been known for long, but it has been shown recently that the 5' poly(A) leaders provide viral mRNAs a translational advantage over the host cell transcripts in infected cells (25). We recently showed that VACV RNA polymerase belongs to the monophyletic group with RNA polymerases encoded by yeast virus-like elements (VLEs), and the VLE promoters are related to those of poxviruses (26). VLE mRNAs also contain 5' poly(A) leaders of variable length that are not complementary to the VLE DNA (27).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A MEME 36 analysis identified and located a significant 19-nt motif (Figure 5a) located approximately 10 bp upstream of the TSS for 36 (out of 36) early gene promoter sequences, which we have called the Early Promoter Motif (EPM). The ASFV EPM is related to the VACV early gene promoter motif ('Upstream Control Element' or UCE) 37,38 as well as the yeast Virus-Like Elements (VLEs) promoters 39 (Supplementary Figure 5.c). Importantly, the distance distribution between the EPM and the TSS is limited to 9-10 bp (Figure 5b Figure 5d).…”
Section: Architecture Of Asfv Gene Promoters and Consensus Elementsmentioning
confidence: 99%